RESPONSE OF RICE AND ASSOCIATED WEEDS TO BIOREGULATOR (BIO HORM) SPRAY AND WEED MANAGEMENT IN SALINITY SOIL - , A.F.; Abou-Hadid; .; M.A. Medany; ; M. Abdrabbo; ; M.K. Hassanein; ; A.A. Farag; S.M. Abolmaaty; ; A.A. Khalil; R.M.H Tagour; G.M Abd El-Hamed; I.M El-Metwally (Arab Universities Journal of Agricultural Sciences, 2010)
Two field experiments were conducted during the two successive seasons of 2007 and 2008 at the Agricultural Experimental Station of Agricultural Research Center, at EL-Serw, Damietta Gover-norate Egypt, to study the effect of the bio horm and weed control treatments (Bentazon, Py-razosoulfuron, Fenoxaprop, Penoxsulam, Bentazon + Fenoxaprop, Bentazon + Penoxsulam, Pyrazosoulfuron + Fenoxaprop, Pyrazosoulfuron + Penoxsulam, twice hand weeding and un- weeded check ) on growth, yield, its components and NPK percentage in grains of direct seeded rice as well as associated weeds in salinity soil. Results illustrated that appli-cation of bio horm increased fresh and dry weight of total weeds. Spraying bio horm after 50 days from sowing (DFS) markedly increased rice growth characters (plant height, number of productive till-ers, fresh and dry weight of rice plants), yield and yield components (panicle length, number of pani-cles/m2, weight of 1000 grain, grain and straw yield) and N, P and K% of grain rice, as compared with untreated treatment. All weed control treat-ments caused significant reduction on number, fresh and dry weight of total weeds/m2 after 60 DFS in both seasons. Pyrazosoulfuron treatment gave the highest decrease in total number of weeds followed by Pyrazosoulfuron + Penoxsulam and Pyrazosoulfuron + Fenoxaprop treatments. Pyrazosoulfuron + Fenoxaprop treatment gave the highest decrease in total fresh weight of weeds followed by Bentazon + Penoxsulam, Pyrazosoul-furon and Pyrazosoulfuron + Penoxsulam, respec-tively in the first season. While, in the second sea-son Pyrazosoulfuron treatment gave the lowest values of total fresh weight of weeds. Meanwhile, Bentazon + Penoxsulam was more effective than other treatments in reducing the dry weight of total weeds in both seasons. All herbicidal treatments and hand weeding increased significantly growth, yield, yield components and chemical composition of grain rice. Bentazon + Penoxsulam was superior treatment for increasing number of productive tillers, number of panicles / m2, 1000- grain weight and grain and straw yield as well as NPK percent-age of rice grains in both seasons. While, the same treatment Bentazon + Penoxsulam recorded the highest values of plant height, fresh and dry weight of whole plant and panical length in the first season. While, Pyrazosoulfuron + Penoxsulam gave the highest increment in plant height, fresh and dry weight of whole plant and straw yield in the second season. The interaction between bio horm and weed management treatments had significant effect on total fresh and dry weight of weeds, num-ber of productive tillers and 1000 grain weight. Pyrazosoulfuron produced the maximum values of number of productive tillers when bio horm was used in the second season, while, application of Bentazon + Penoxsulam gave the highest values of 1000 grain weight when bio horm was used in the second season. It could be concluded that using the bioregulator (bio horm) resulted in incre-ment of growth and productivity of rice crop under salinity soils. Using the combinations of herbicides caused more reduction of weeds and increased rice grain yield.